1956
DOI: 10.1111/j.1151-2916.1956.tb15645.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Stabilization of Zirconia

Abstract: The characteristics of magnesia-, calcia-, and ceria-stabilized zirconia are described. They were determined by two techniques: (1) the National Bureau of Standards high-temperature X-ray analysis of sintered specimens and (2) room-temperature X-ray analysis of specimens heat-treated at 118OOC. up to 100 hours. Also reported is an investigation of the ternary system Ti-Zr-0, with particular emphasis on the binary systems TiO-ZrOz and Ti-ZrOz. Data are presented on the stability of the compound ZrTi04 and on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

1964
1964
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 22 publications
0
33
0
1
Order By: Relevance
“…Such effect of small amount of titanium in zirconia ceramics was reported more than 50 years ago [7], but at that time, convenient ceramic powder with several hundred micron crystallites size and metallic powder with comparable grain size were used. In our case, with tiny size of ceramic crystallites, another method of metal particle addition was implemented; fragments of ZrO 2 /CNTs aerogels were immersed in AgNO 3 solution and exposed to ultraviolet radiation with simultaneous sonication for process homogeneity.…”
Section: Figmentioning
confidence: 98%
“…Such effect of small amount of titanium in zirconia ceramics was reported more than 50 years ago [7], but at that time, convenient ceramic powder with several hundred micron crystallites size and metallic powder with comparable grain size were used. In our case, with tiny size of ceramic crystallites, another method of metal particle addition was implemented; fragments of ZrO 2 /CNTs aerogels were immersed in AgNO 3 solution and exposed to ultraviolet radiation with simultaneous sonication for process homogeneity.…”
Section: Figmentioning
confidence: 98%
“…Webber at al. [9] showed the partial limited solubility of Ti into ZrO 2 and the effect of the blackening of zirconia through the formation of oxygen deficiencies [9]. The research conducted by Ruh [10] showed that the maximum quantity of titanium was dissolved in the ZrO 2 in an amount about 4 at.%.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the partial solubility of titanium along the grain boundaries of ZrO 2 without creation of the new phase was found on the based on many studies [8][9][10]. Webber at al.…”
Section: Introductionmentioning
confidence: 99%
“…The study of reaction between zirconia and titanium was subject of the many researches. The first studies of the ZrO 2 -Ti system were carried out for the stabilization of zirconia by various kinds of dopants and the reaction of liquid titanium and its alloys due to the problem with ceramic molds for casting [14,15]. The observations of the reaction between titanium and ZrO 2 led to further studies at temperatures below the melting point of titanium [16,17].…”
Section: Introductionmentioning
confidence: 99%